Tata Kelola Perusahaan dan Audit Report Lag pada Perusahaan Financial yang Terdaftar di Bursa Efek Indonesia - Serly Serly (Politeknik Ganesha Medan, 2021)
This research seeks to examine the factors that affect the audit report lag of financial companies during the period of 2014-2018. Several factors are selected under this study consists of audit quality, audit committee, auditor changes, board of directors, frequency of board meetings, ability of board of directors, gender of board of directors, risk management committee, company size, and loss. 86 financial companies are sampled in this study. The researcher gained the data using purposive sampling method. The findings indicate the financial company listed in Indonesian Stock Exchange need the average of 71 days to submit audit financial report after the closing date. The variable of frequency of board meetings has significant positive response for the audit report lag, while the impact of board of directors and risk management committee is negative. Meanwhile, variables of the audit quality, audit committee, auditor changes, director expertise, board gender diversity, company size, and loss did not show significant influence on audit report lag. Overall, the finding in this study provides that monitoring activities through board meeting will allow management to discuss how to improve company performance and also reduced the delay corporate disclosure information to stakeholder.